USING CRITICAL INFRASTRUCTURE AS A STRATEGIC RESOURCE FOR IMPROVING THE COMPETITIVENESS OF THE STATE - YAREMENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article explores the theoretical and practical aspects of protecting critical infrastructure as a strategic resource for improving the competitiveness of the state. In the article, the concept of critical infrastructure is defined and justified as a strategic resource for improving the competitiveness of the state. Also, a number of threats are identified that can affect the functioning of objects of critical infrastructure and cause instability at different levels, including national security, which significantly affects the competitiveness of the state. One of the directions for ensuring effective protection of critical infrastructure is to develop a policy of “efficiency” - to optimize the distribution and application of state security resources for localizing potential sources of threat and enhancing the competitiveness of the state. The approach to formulating content of the concept of “threat” in the context of competitiveness of the state is analyzed and improved. The focus is on identifying critical objects on national, regional and local levels of infrastructure as a strategic resource for improving the competitiveness of the state. The methodology for attributing objects of national infrastructure to the field of critical infrastructure in accordance with their importance functions and services that they perform is described. A list of vitally important functions and services provided by representatives that require protection is presented, as well as representatives that are objects of critical infrastructure in the context of national security and competitiveness of the state. The content of relevant normative-legal acts that provided grounds for specifying a list of threats to critical infrastructure and confirming its inclusion in strategic resources for ensuring national security and enhancing competitiveness of the state is analyzed. Based on a critical analysis, it is generalized that there are three main categories of threats to critical infrastructure: natural origin, technological nature and malicious actions. It is proposed to supplement this list with combined threats that can cause “synergy effect” destabilization of critical infrastructure, reducing competitiveness of the state.
Keywords: competitiveness; critical infrastructure; strategy; challenges and threats; security; the state paradigm of security and competitiveness